ORGANIZATIONAL ISSUES OF AUDIT IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
This article is devoted to the issues of improving the organization of audit in the practice of Uzbekistan. The introductory part of the article reveals the essence of the organization and conduct of audit in the Republic and the relevance of research in this area. It also describes the research methods used to cover the content of the article, a review of the relevant literature, an analysis of the main indicators of audit activity in Uzbekistan, practical problems of organizing audit, organizational stages of audit, and conclusions reached as a result of the research.